Synthesis of carboxy-cyclobutane isomers combining an amide bond and self-assembly of coordination polymers in the solid state: controlling the reaction site of [2 + 2] cycloaddition by introducing a substituent group. Issue 8 (10th February 2021) - Zhu, Rong-Rong; Wang, Tao; Zhao, Lijia; He, Liancheng; Gao, Feng; Du, Lin; Zhao, Qi-Hua
Abstract : Combining an amide bond and self-assembly of CPs by solid-state [2 + 2] cycloaddition reactions to synthesize stereoselectively carboxy-cyclobutane isomers. Abstract : A pair of carboxy-cyclobutane isomers were synthesized stereoselectively using a method that combined reversible amide bond formation and self-assembly of coordination polymers (CPs) via solid-state photochemical [2 + 2] cycloaddition reactions. Amide bond formation occurred by the condensation of amino and carboxy groups to prepare a pyridine-amide ligand, while pyridine-amide CPs were constructed by the self-assembly of metal ions, pyridine-amide, and auxiliary ligands for the solid-state [2 + 2] photodimerization during the second step. The pyridine-amide ligand underwent the [2 + 2] cycloaddition reaction in 2D CPs to generate amide-cyclobutane derivatives stereoselectively that were afforded by removing metal ions and auxiliary ligands under alkaline conditions. The carboxy-cyclobutane isomers were successfully synthesized by the hydrolysis of the amide-cyclobutane derivatives. Moreover, the second amide-cyclobutane derivative and carboxy-cyclobutane derivative were obtained stereoselectively via regulating the reaction site of [2 + 2] cycloaddition by introducing a substituent group in the auxiliary ligand.